Rancang Bangun Sistem IoT untuk Monitoring Ketinggian Air Sungai Menggunakan NodeMCU dan Sensor Ultrasonik HC-SR04 Terintegrasi Website - Darel Trescanaya; Yayak Kartika Sari; Mohamad Khoirul Ansor (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to design and build an Internet of Things (IoT)-based river water level monitoring system using NodeMCU ESP8266 and HC-SR04 ultrasonic sensor integrated with a website in Semarum Village, Durenan District, Trenggalek Regency. The system was developed using the Rapid Application Development (RAD) method with the Laravel framework and MySQL database. Data collection techniques include observation, interviews, literature studies, experiments, and documentation. Data analysis was carried out through functional testing of the system using Black Box Testing, sensor accuracy analysis using Mean Absolute Percentage Error (MAPE), and analysis of WhatsApp notification response time. The results showed that the system was able to read the water level automatically every minute, display data in real-time via the website, and send WhatsApp notifications automatically when alert or danger status. The results of Black Box Testing showed that all system features functioned well. Accuracy testing produced a MAPE value of 1.027% with an average accuracy rate of 98.97%, while WhatsApp notification testing showed a 100% success rate with an average delay of around 50 seconds. This system is equipped with three water condition indicators (SAFE, ALERT, and DANGER) as well as multi-user management features which are an added value compared to previous research.